Empowerment Of Community Business Of Scavengers In Landfill Of Njawar, Surabaya City - Prasetijowati, Tri; Setyarahajoe, Ratna; ., Suminah; ., Sapja (Advances in Social Sciences Research Journal, 2018)
Surabaya, the second largest city in Indonesia, has a large scale garbage disposal site or landfill located in Njawar. It is commonly called Njawar Landfill. In this landfill area there are many communities of scavengers living in some villages not far from the landfill site. Although they live in various limitations, still they are able to show their high survival rate due to their assets or potential. During the field identification towards the scavengers, some physical, financial, human resources, and social capital and waste assets have been found. They are still considered in a low condition, except for the waste assets, so that they have less role in finding and developing some activities for the business empowerment of the scavenger community. This research was conducted by combining the quantitative and qualitative methods, and data collection techniques were carried out through questionnaires, observations, interviews and FGDs with the scavenger communities. A simple random technique using confidence intervals was applied for sampling in this study. There were several deep consideration due to the business empowerment for the scavengers of Njawar landfill, and they included the low technology, low income and the exploitation of the collectors on the scavengers. Three dimensions of opportunity, scavenger HR, and accessibility of business sources had been determined for the proposed activities to build the business empowerment of the scavengers. Keywords: business empowerment, scavengers.